Challenges on Student Health Information Records: A Basis for System Development - Sison, Harley David M.; Supena, Charish Anne G.; Tapang, Yvan Kenneth V.; Tomas, Charmaine I.; Urbano, Raquel S.; Yacat, Germielyn S.; Paet, Roseann (UM Purwokerto Press, 2025)
Student health records play a pivotal role in nursing education, offering a comprehensive insight into students' health histories, immunization statuses, and clinical experiences. This study aims to identify the challenges and specific needs of NEUST-CON students to develop an efficient health record management system, design an Electronic Medical Record that outlines data collection, storage, security, and access protocols, and create a system prototype incorporating essential features and functionalities based on user requirements. This study utilizes applied quantitative research to gather numerical data, objectively measuring factors like the frequency and impact of issues related to record accessibility, availability, data retrieval and update, and data security and privacy. Furthermore, it employs a descriptive correlational design to examine the relationships between the demographic profile and the challenges on the student health information record system among NEUST-CON students. Findings revealed that most nursing students at NEUST are female, aged 18 to 21, primarily in their first year. The study identified challenges related to availability, accessibility, data retrieval and update, and data security and privacy in student health information records. Notably, availability emerged as the most pressing challenge. While overall satisfaction was reported among respondents, data security and privacy concerns persisted. A significant relationship was also observed between students' year levels and ages. Therefore, enhancements in infrastructure and functionalities are essential to ensure consistent availability of data and resources, mitigating downtime and ensuring uninterrupted access to the SHIR prototype system.